Integrated Thematic Learning during COVID-19 Pandemic - Maya Agustina; Tengku Hafinda; Suharman Suharman (AL-ISHLAH: Jurnal Pendidikan, 2022)
The present study was driven by the conditions of students and teachers encountering challenges while implementing integrated thematic learning, notably during the online classroom activities. This study aimed at identifying the planning, implementation, and evaluation of integrated thematic learning. Mixed Methods were employed as the research design. The class teachers (thematic teachers) and headmaster of MIN Kota Banda Aceh were recruited as the investigative participants. Quantitatively, the data were collected through questionnaire administration based on Likert. Qualitatively, interviews were performed to gain more qualitative data. The participants were the thematic teachers and the headmasters of MIN 11 and 6 Banda Aceh. The findings reported that the thematic teachers of MIN 11 and 6 were able to design lesson plans effectively. Although the COVID 19 forced them to implement and evaluate integrated thematic learning online, they could perform them well. In particular, they argued that the activities were very good (55%) and good enough (44%). On the other hand, the teachers of MIN 6 and 11 faced challenges while actualizing thematic learning. Those challenges were encountered when the participants began their learning experiences of teaching in the post-pandemic.